2019
DOI: 10.1177/0950017019828904
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction and Bad Jobs: Why Are Cleaners So Happy at Work?

Abstract: Our analysis is based on the French DARES Working Conditions survey which contains a very large sample of individuals representative of the French working population. We demonstrate that employees working in the cleaning sector report significantly higher levels of satisfaction than the other employees. This statistical result is robust; it persists when we introduce a large number of control variables. This result is puzzling insofar as it is generally agreed that these workers hold ‘poor quality’ jobs: low p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 37 publications
(64 reference statements)
1
27
0
2
Order By: Relevance
“…Future research could extend the existing literature considerably by theoretically and empirically articulating the importance of the objective and subjective dimensions of job quality and the significance of life stages (Lené, 2019). Future studies could also examine the experiences of different groups of workers, including permanent residents versus temporary migrants, more explicitly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research could extend the existing literature considerably by theoretically and empirically articulating the importance of the objective and subjective dimensions of job quality and the significance of life stages (Lené, 2019). Future studies could also examine the experiences of different groups of workers, including permanent residents versus temporary migrants, more explicitly.…”
Section: Resultsmentioning
confidence: 99%
“…Subjective indicators focus on worker perceptions of the job and the extent to which that job meets their personal needs (Brown et al., 2007; Eurofound, 2012). Some studies have found that workers’ assessments of job quality vary depending on their life stage and their personal circumstances (Knox et al., 2015; Lené, 2019; Pocock and Skinner, 2012). The subjective approach is underpinned by the notion that worker preferences and their alignment with job characteristics are critical.…”
Section: Current Debates On Defining and Measuring Job Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…relatively high levels of satisfaction with low-paying jobs implying arduous work) with reference to the workers' life and employment history, such as migration or adaptation to difficult circumstances (e.g. Léné, 2019). 4.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, we found only two comparative studies across occupational categories. One is situated in France (Léné, 2016) while the other is in Jordan (Al-Zoubi, 2012). Additionally, research on determinants of job satisfaction for specific occupational categories (e.g.…”
mentioning
confidence: 99%